Quranic knowledge and integrity of behavior (an analytical Quranic study) (Journal of Imam Al-Kadhim College, 2025)
The research intended to explain the importance of Quranic knowledge and its impact on straightforwardness of behavior by examining it from all aspects with the aim of exploring and identifying Quranic truths according to an inductive and analytical approach, as it is clear that the Holy Qur’an has paid a great attention to the issue of straightforwardness, whether it is on the rational level, or on the behavioral level, the latter one is our concern in this study. The Almighty God has mentioned many Qur’anic evidences and proofs for this, which contribute to achieving the highest levels of human perfection and existential levels, and this is what we will address in detail in the demands of this objective research by explaining the types of Qur’anic knowledge and their impact on straightforwardness behavior.
Keywords: knowledge, the Qur’an, Quranic knowledge, integrity, behavior, straightforwardness behavior